The role of the domestic law of the host state in determining the jurisdiction ratione materiae of investment treaty tribunals : the partial revival of the localisation theory? - Eftekhar, Reza, 1986- (Nijhoff international investment law series, 2021)
"This book focuses on the role of the host state law in determining the jurisdiction ratione materiae of investment treaty tribunals. Given domestic law's essential role in subject-matter jurisdiction issues, and in the light of the broader function of host state law and host state courts in contemporary investment treaty law, the author argues that the dormant 'localisation' theory that was raised and defended by developing countries in the 1960s-1970s in the context of foreign investment contract disputes has now been partially revived in the area of investment treaty law"--